Microbiota fermentation-NLRP3 axis shapes the impact of dietary fibres on intestinal inflammation. Issue 10 (22nd January 2019) - Singh, Vishal; Yeoh, Beng San; Walker, Rachel E; Xiao, Xia; Saha, Piu; Golonka, Rachel M; Cai, Jingwei; Bretin, Alexis Charles Andre; Cheng, Xi; Liu, Qing; Flythe, Michael D; Chassaing, Benoit; et al.
Abstract : Objective: Diets rich in fermentable fibres provide an array of health benefits; however, many patients with IBD report poor tolerance to fermentable fibre-rich foods. Intervention studies with dietary fibres in murine models of colonic inflammation have yielded conflicting results on whether fibres ameliorate or exacerbate IBD. Herein, we examined how replacing the insoluble fibre, cellulose, with the fermentable fibres, inulin or pectin, impacted murine colitis resulting from immune dysregulation via inhibition of interleukin (IL)-10 signalling and/or innate immune deficiency ( Tlr5 KO). Design: Mice were fed with diet containing either cellulose, inulin or pectin and subjected to weekly injections of an IL-10 receptor (αIL-10R) neutralising antibody. Colitis development was examined by serological, biochemical, histological and immunological parameters. Results: Inulin potentiated the severity of αIL10R-induced colitis, while pectin ameliorated the disease. Such exacerbation of colitis following inulin feeding was associated with enrichment of butyrate-producing bacteria and elevated levels of caecal butyrate. Blockade of butyrate production by either metronidazole or hops β-acids ameliorated colitis severity in inulin-fed mice, whereas augmenting caecal butyrate via tributyrin increased colitis severity in cellulose containing diet-fed mice. Elevated butyrate levels were associated with increased IL-1β activity, while inhibition of the NOD-like receptor protein 3 by genetic, pharmacologic or dietary means markedly reduced colitis. Conclusion: These results not only support the notion that fermentable fibres have the potential to ameliorate colitis but also caution that, in some contexts, prebiotic fibres can lead to gut dysbiosis and surfeit colonic butyrate that might exacerbate IBD.